Advanced electrospun nanofibers as bifunctional electrocatalysts for flexible metal-air (O2) batteries: Opportunities and challenges. (February 2022) - Li, Shujing; Guo, Hongtao; He, Shuijian; Yang, Haoqi; Liu, Kunming; Duan, Gaigai; Jiang, Shaohua
Graphical abstract: Highlights: The recent progress of electrospun nanofibers as electrocatalysts for flexible metal-air batteries has been reviewed. The fundamental principles of electrospinning technique have been introduced. The importance of bifunctional electrocatalysts for oxygen reduction and oxygen evolution in metal-air batteries has been highlighted. Future perspectives of novel electrospun nanofibers composite for flexible metal-air batteries have been proposed. Abstract: Rechargeable metal-air (O2 ) batteries have been regarded as the promising candidates for wearable and flexible energy devices owing to their outstanding energy density, low cost, and high safety. Generally, the electrocatalyst at air cathode plays a significant role in various metal-air (O2 ) batteries. As a versatile and efficient technique, electrospinning has been considered as a powerful method to fabricate nanofibers, which hold great potential as bifunctional electrocatalysts for such batteries. Although great progresses have been achieved in improving the electrochemical performance of catalysts in recent years, some critical challenges still maintain. In this review, the advanced electrospun carbon nanofiber-based electrocatalysts for flexible metal-air batteries have been summarized. Then, additional discussions have been included focusing on the advantages and characteristics of different nanofibers and some special requirements for various flexible metal-air batteries. Moreover, some current challenges and future prospects in the development of electrospun carbon nanomaterials for flexible metal-air cathode catalysts have been rationally analyzed.